2006
DOI: 10.4049/jimmunol.177.9.6081
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Differentiation of Antigen-Specific CD8 T Cells in Tumor-Draining Lymph Nodes

Abstract: CD8 T cells lacking effector activity have been recovered from lymphoid organs of mice and patients with progressing tumors. We explored the basis for lack of effector activity in tumor-bearing mice by evaluating Ag presentation and CD8 T cell function in lymphoid organs over the course of tumor outgrowth. Early after tumor injection, cross-presentation by bone marrow-derived APC was necessary for T cell activation, inducing proliferation and differentiation into IFN-γ-producing, cytolytic effectors. At later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 54 publications
(70 reference statements)
4
71
0
Order By: Relevance
“…In their study, melanoma-derived factors actually enhanced LPS-induced expression of select costimulatory molecules on DC2.4 cells, although cytokine and chemokine profiles were not assessed. Importantly, that previous study evaluated the effects of TCM derived from B16-F10, a different variant of B16 melanoma than the B16-F1 line that is associated with dysfunctional CD8 + T cell responses in vivo (Hargadon et al, 2006) and that suppresses DC maturation and activation in our current study. Additionally, we have recently demonstrated that a chemically mutated variant of B16, the poorly tumorigenic D5.1G4 melanoma, is significantly less immunosuppressive than B16-F1 with respect to the influence of tumor-derived factors on DC2.4 maturation and activation (Hargadon et al, 2012).…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In their study, melanoma-derived factors actually enhanced LPS-induced expression of select costimulatory molecules on DC2.4 cells, although cytokine and chemokine profiles were not assessed. Importantly, that previous study evaluated the effects of TCM derived from B16-F10, a different variant of B16 melanoma than the B16-F1 line that is associated with dysfunctional CD8 + T cell responses in vivo (Hargadon et al, 2006) and that suppresses DC maturation and activation in our current study. Additionally, we have recently demonstrated that a chemically mutated variant of B16, the poorly tumorigenic D5.1G4 melanoma, is significantly less immunosuppressive than B16-F1 with respect to the influence of tumor-derived factors on DC2.4 maturation and activation (Hargadon et al, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…This tumor has also been shown to induce dysfunctional anti-tumor CD8 + T cell responses (Hargadon et al, 2006) that are similar to those often observed in melanoma patients Anichini et al, 2003;Zippelius et al, 2004) and it has been suggested that this dysfunction may arise from an influence of the tumor on the functional quality of DC. Because of the inherent difficulties in isolating tumor-associated DC from B16-F1 tumor-bearing animals, though, it has thus far not been possible to thoroughly examine the nature of these cells.…”
Section: The Influence Of B16-f1 Melanoma-derived Factors On Lps-indumentioning
confidence: 79%
See 3 more Smart Citations